Analisis Blow-by Tinggi Pada Traktor New Holland T7.150 - sunaryo, sunaryo; mutaqin, dimas ahmad; hakim, legisnal (Universitas Muhammadiyah Metro, 2024)
Tractor is a tool that is often used in the process of agricultural land processing, a vehicle specially designed to handle heavy pulls at low speeds, or to pull special implements needed in agricultural activities. The use of tractors on a large enough land must of course carry out routine maintenance, especially on engines which have a limited operating time, within a certain limit it is necessary to check the components after reaching the maximum time limit. This analysis was carried out during November 2023 - February 2024. Secondary data collection was carried out by making direct observations on the Newholland T7.150 Tractor unit during the design and operation of the unit. Identification is carried out while the unit is operating, this aims to determine the effectiveness of the engine on the tractor, the occurrence of high blow-by engines and the factors that cause them. The blow-by pressure test results showed that the blow-by pressure in the engine was at a level far exceeding the maximum limit of 20.42 cm H2O (8.047 In H2O), indicating a serious problem with the sealing between the piston and cylinder. When the compression test was carried out, normal compression results were found, indicating that the compression pressure in the engine was stable at a level in line with normal standards, also indicating that the components in the combustion system were functioning properly. From the analysis, phenomena related to high blow-by caused by improper ring gap and valve seal leakage in the engine were investigated. The analysis shows that the out-of-specification ring gap and leakage at the valve seal can result in uncontrolled leakage of fuel and combustion gases into the engine crankcase.